Dynamics Analysis of Steel Ball for Planar Sinusoidal Steel Ball Transmission Mechanism - Meiqiu Li; Jingbo Luo; Bingbing Wang; Ning Li (Jixie chuandong)
The planar sinusoidal steel ball transmission mechanism with fixed disk output and retainer fixed and no eccentric is studied， which has good heat dissipation and make up for the shortage of cylindrical sinusoidal movable teeth transmission mechanism. By establishing the mechanical model of the steel ball in the planar sine ball transmission mechanism，the change law of the contact force and inertia force are obtained at the same time，and the accuracy of the mechanical model is verified by the simulation， which provides the theoretical basis for the strength checking and the vibration analysis of the mechanism.